Chapter 6 Everyday Symphonism Boris Asafiev's Soviet Theory of Popular Music - Viljanen, Elina (Taylor & Francis, 2023)
Stalin's political takeover of the cultural theoretical pattern of Bolshevik novyy byt 'new public life' created a powerful myth of the total repression of 'bourgeois' philosophy in the early 1930s. However, since the 1920s novyy byt had also produced directives governing the formation of new theories of ideologically correct 'spiritual kul'turnost' (culturality, being civilized) on the basis of 'the best achievements of bourgeois traditions.' Classical music represented one of these achievements. The chapter sheds light on the idealist philosophical sides of the Soviet conception of kul'turnost. Looking at the musicologist Boris Asafiev (1884-1949) as an intellectual whose theoretical strategies shaped Soviet culture during the Stalin era, the author shows that the Soviet conception of classical music as a symbol of kul'turnost developed from the late 'Silver Age' philosophy of 'internal' spiritual life. Shaped by the NEP-era Bolshevik discourse of novyy byt and Pan-European cultural and musical theories, the conception emerged during the Stalinist kul'turnost campaigns. Asafiev renewed his theoretical setting (theory of Intonation) of the 1920s to suit Stalinist ideological outlines of what a 'socialist approach' to the arts ought to be. However, his theory was one of the evolving ideas that managed to accomplish this in a way that produced interesting scholarly results. His apology of classical music constitute an interesting intellectual history of Russian appreciation of classical music as a proper type of Russian kul'turnost and explains the Soviet understanding of popular music.